Adherence to antihypertensive treatment and associated factors among patients on follow up at University of Gondar Hospital, Northwest Ethiopia - Ambaw, Abere Dessie; Alemie, Getahun Asres; W/Yohannes, Solomon Meseret; Mengesha, Zelalem Birhanu (BMC public health, 2012)
Background Hypertension is an overwhelming global challenge with high morbidity and mortality rates. The prevalence of HTN is estimated to be 6% in Ethiopia and 30% in Addis Ababa. Poor adherence is associated with bad outcome of the disease and wastage of healthcare resources. In Ethiopia, particularly in the study area little is known about treatment adherence and associated factors. Therefore this study aimed to assess adherence to antihypertensive therapy and associated factors among HTN patients on follow up at University of Gondar Referral Hospital. Method Institution based cross sectional study was conducted. Systematic sampling technique was used to select 384 participants. A structured standard questionnaire was used after some modifications. Morisky Medication Adherence Scale was used for labeling patients as adherent or non-adherent. Data were entered and analyzed using SPSS version 16. Results More than half (64.6 %) of the study participants were found to be adherent to their treatment. Sex (AOR = 0.48, 95%CI = 0.28, 0.82), knowledge about HTN and its treatment (AOR = 6.21, 95%CI = 3.22, 11.97), distance from the hospital (AOR = 2.02, 95% CI =1.19-3.43) and co morbidity (AOR = 2.5, 95%CI = 1.01, 6.21) variables were found significantly associated with treatment adherence. Conclusion Only 64.6% of the study subjects were found to be adherent to their treatment. Factors such as sex, distance from the hospital, number of co morbidities, Knowledge about HTN and its treatment were associated with adherence behavior of patients. Early diagnosis and management of co morbidities, adherence counseling and patient education about the disease and its treatment are important to improve adherence status of patients.